2019
DOI: 10.1161/strokeaha.118.024091
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interhospital Transfer on Endovascular Treatment for Acute Ischemic Stroke

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
97
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 28 publications
4
97
2
2
Order By: Relevance
“…[29][30][31][32][33][34][35][36] Direct transportation to intervention centers may be preferable to interhospital transfers, which can be associated with delays in treatment and worse outcomes. 23,[37][38][39] The designation of additional endovascular centers in underserved areas may be part of the solution, although it may be challenging to maintain a roster of staff and neurocritical care services in such areas, and one Korean study found that outcomes were worse at small-volume compared to large-volume sites. 40 Finally, allowing patients to seek care across provincial boundaries may reduce travel time to stroke care services.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32][33][34][35][36] Direct transportation to intervention centers may be preferable to interhospital transfers, which can be associated with delays in treatment and worse outcomes. 23,[37][38][39] The designation of additional endovascular centers in underserved areas may be part of the solution, although it may be challenging to maintain a roster of staff and neurocritical care services in such areas, and one Korean study found that outcomes were worse at small-volume compared to large-volume sites. 40 Finally, allowing patients to seek care across provincial boundaries may reduce travel time to stroke care services.…”
Section: Discussionmentioning
confidence: 99%
“…An Australian study based in Victoria found no difference in 90-day functional outcomes between transferred and direct to CSC presenters undergoing EVT9; however, international registries have demonstrated poorer outcomes in transferred patients 10–12. New South Wales and other Australian states have different geographical challenges from Victoria.…”
Section: Introductionmentioning
confidence: 99%
“…Previous post hoc analyses of prospective cohort studies have shown that for patients with an LVO of the anterior circulation, in general, it is beneficial to be directly presented to a CSC, as opposed to being transferred from a PSC. Venema et al, who also used data from the MR CLEAN Registry (part I), found that patients directly presented to a CSC had a 40-min shorter OGT and a 57-min shorter FDGT than transferred patients [3]. The authors also found a negative effect of inter-hospital transfer on the likelihood of functioning independently at 90 days post-stroke (OR: 0.69, 95% CI 0.54-0.89).…”
Section: Discussionmentioning
confidence: 99%
“…Patients who are eligible for EVT are subsequently transferred to a comprehensive stroke center (CSC). Studies show that this 'dripand-ship' system delays initiation of EVT by 40-106 min and decreases the chance of a good clinical outcome by approximately 10% [3][4][5]. Despite this clear disadvantage, the 'drip-and-ship' system is currently the most feasible, because accurately diagnosing an LVO in the prehospital setting is challenging.…”
Section: Introductionmentioning
confidence: 99%